Sentiment Analysis of Climate Action Issues on Twitter Using Orange Data Mining - Resti Kinanthi; Nindyta Aisyah Dwityas (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The 2030 Sustainable Development Goals (SDGs) related to climate change are multidimensional issues that impact all aspects of society, including public health and human rights. To understand how a group views the issue of climate action, it is necessary to identify the opinions they express to develop appropriate climate action strategies with direct community involvement. This study aims to capture public discussions, especially from young people, regarding climate action on Twitter. The data used in this study were collected from Twitter social media tweets using an Application Programming Interface (API) provided by Twitter developers. Through scraping techniques or data collection stages, this study used Orange Data Mining software to collect tweet data about climate action from July 14-21, 2022. The results of study revealed that there are four issues discussed by the younger generation regarding climate action on Twitter including: the core issues about climate change and global warming, urgency on climate action, attention to the causes and consequences, and responsibility and solutions to climate change through the climate action movement. Sentiment analysis showed that 74.42% (6,716 tweets) expressed positive sentiment toward climate action, while 25.58% (2,308 tweets) expressed negative sentiment. The implication of this research for framing theory is that the dominant frame in public discourse can influence policy acceptance and collective action. Policymakers and communicators can strategically reinforce constructive frames for young people, such as economic opportunity, equity, and innovation, to broaden youth engagement while reducing resistance to the impacts of climate change. As the largest Muslim country, the results of this study provide an important contribution to the internal dynamics of religious environmental activism among the younger generation in responding to the environmental and climate crisis.